Professional preparedness as an incredible component of successful professional activity of the person - Sirokha, Lilya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The historical aspect and the essence of the term of readiness for work as a special mental state; a necessary and extremely important component of a successful professional life of a person is studied in the article. Readiness for a certain phenomenon helps person to adapt more quickly and to fulfill his duties more successfully. It contributes to the development of personality. The author points out that an analysis of the problem of readiness shows that the genesis of this concept is related to the development and understanding of the concept of "psychological readiness for work". It can be defined as permanent (as a result of labor education) or temporary (as a result of psychological training or psychological mobilization during this period) mental condition, which is caused due to the need for work. The question of the readiness of a specialist for professional activity is studied within such sciences as: psychology, pedagogy, philosophy. The author’s determination of readiness is formulated during the conduction of the research. The author proposes to understand the readiness as a complex integrative formation, characterizing a particular mental state. It is a necessary and essential component of a successful professional life of the individual. It helps a person to adapt more quickly, to fulfill his professional duties more successfully; it promotes professional development of a specialist. Readiness includes not only professional characteristics and skills, but either personal trait. The conclusion is made that since readiness is a dynamic value, it means that its course is determined by age, by learning experience, individual abilities of the person and so on. The author summarizes the importance of the development of psychological readiness for work during the formation of the personality of a modern specialist. It is emphasized that professional readiness cannot be the same as a subjective professional readiness. According to the modern scientific researches the author distinguishes particular levels of professional readiness, such as: high (autonomy in setting and solving new tasks, adequacy of assessment and self-assessment of professionally important qualities, ability to effectively solve problems during time deficit, etc.); average (average level of expression of the mentioned qualities); and low (inability to set and solve complex problems independently, inadequate assessment and self-assessment of professionally important features, etc.